2021
DOI: 10.2147/jmdh.s240563
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Principles and Anesthesiology Clinical Practice: Current Perspectives

Abstract: Background Palliative care is a person-centered approach aiming to relieve patient’s health-related suffering and it is often needed when caring for critically ill patients to manage symptoms and identify goals of care. Aim To describe the integration of palliative care principles in anesthesiology clinical practice, within and outside the ICU and to analyze the additional challenges that COVID-19 pandemic is posing in this context. Methods F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 97 publications
0
7
0
1
Order By: Relevance
“…In this scenario, providing timely palliative interventions with adequate symptoms relief represents a major issue 13 . However, it has been reported that more than half of all patients with a DNI order who receive non-invasive respiratory support for AHRF survive to hospital discharge-often with no worse quality of life compared to those with no ceiling to treatment escalation 15 .…”
Section: Hfno and Inspiratory Effort Dni Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, providing timely palliative interventions with adequate symptoms relief represents a major issue 13 . However, it has been reported that more than half of all patients with a DNI order who receive non-invasive respiratory support for AHRF survive to hospital discharge-often with no worse quality of life compared to those with no ceiling to treatment escalation 15 .…”
Section: Hfno and Inspiratory Effort Dni Patientsmentioning
confidence: 99%
“…Moreover, Bräunlich et al speci cally investigated the effect of HFNO on inspiratory effort as assessed by esophageal manometry in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) 12 showing a signi cant reduction in respiratory rate, inspiratory effort, and work of breathing. In this scenario, HFNO therapy can play a valuable role in managing the respiratory needs of patients who receive a "Do Not Intubate" (DNI) order, aligning with the goals of care outlined in the ceiling to treatment escalation 13 . Goals of care that preclude intubation and mechanical ventilation (MV) are more frequently decided by patients suffering from AHRF; thus, the individualization of the therapeutic approaches employed to support respiratory function is of pivotal importance to respect patient's preferences and improve quality of life 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the ICU setting is burdened by high mortality and high suffering, providing palliative care to critically ill patients and their families is a major goal of ICU care [13]. Palliative care aims to maintain and improve the quality of life of all patients and their families at any stage of life-threatening illness [14].…”
Section: Timing Of Palliative Care Initiation In Icumentioning
confidence: 99%
“…Decision-making, alignment of treatment with the patient's goals, emotional support for families, and the basics of symptom management are core elements of palliative care and should be routine aspects of critical care [15]. Studies have shown that integration of palliative care in the ICU improves quality of life, shortens hospital and ICU length of stay, lowers the care-giver burden, and reduces the use of emergency resources [13,[16][17][18][19].…”
Section: Timing Of Palliative Care Initiation In Icumentioning
confidence: 99%
“…Additionally, comorbid and frail patients may experience an even worse course [ 2 ], with difficult hospital stay, sometimes requiring postsurgical intensive care unit (ICU) admission. Peculiar management is expected for patients with anticipated poor prognosis, as aggressive therapeutical approaches would not determine a full restoration of organ function, and life expectancy may not be affected by curative care [ 3 ]. In this light, ICU admission may be considered inappropriate.…”
Section: Introductionmentioning
confidence: 99%